THE GROWTH KINETICS AND TOTAL LIPID CONTENT OF Thalassiosira sp. (BACILLARIOPHYCEAE) UNDER MIXOTROPHIC CONDITIONS - Nodque, Kelee Ira Burgan; Dionela, Cleresa Salido; Huervana, Fredson Hervias; Traifalgar, Rex Ferdinand Mallare (Indonesian Aquaculture Journal, 2024)
Conventional microalgae culture is challenged by issues of light limitation and cell self-shading. This study aims to evaluate the impact of different cultivation modes on the growth and lipid content of Thalassiosira sp. The diatom, Thalassiosira sp., was grown in autotrophic, mixotrophic-suspended, and mixotrophic-biofilm conditions until the stationary phase was reached. After four (4) days of culture, analysis of the cell densities revealed a significant difference between groups, with cell densities of 7.3×105 cells mL-1 for control, 1.1×106 cells mL-1 for mixotrophic-suspended, and 1.9×106 cells mL-1 for mixotrophic-biofilm cultures. Both treatments are significantly higher than the control. However, mixotrophic-biofilm culture achieved the highest cell density among all cultivation modes, 161.81% higher than the control. The specific growth rate (SGR) of Thalassiosira sp. in mixotrophic-biofilm culture was highest among treatments, while the doubling time was significantly highest in the control. Moreover, mixotrophic-biofilm culture attained the highest biomass at 56 mg 100 mL-1. Thalassiosira sp. cultured under mixotrophic-biofilm also recorded the highest lipid content at 9.89%. It is both significantly higher than the control (3.06%) and the mixotrophic-suspended culture (6.15%). The cell density, algal biomass, and lipid content of Thalassiosira sp. under mixotrophic-biofilm culture highlight this culture strategy’s promising potential in improving microalgae growth and lipid content, ridding of light as an indispensable growth factor.